Case Report: A successful outcome of nadroparin calcium therapy for cerebral venous sinus thrombosis in a child with acute lymphoblastic leukemia - Xie, Lichun; Xu, Ye; Zhou, Guichi; Chen, Fen; Li, Changgang; Ma, Lian; Wen, Feiqiu (Frontiers in Pediatrics, 2024)
Background: The appearance of cerebral venous sinus thrombosis (CVST) in childhood acute lymphocytic leukemia (ALL) is a rare life-threatening disease that can cause significant morbidity, neurological sequela, and potentially poor outcomes.Case presentation: We present the case of a 13-year-old male with ALL who developed CVST and intrinsic hemorrhagic approximately 30 days after receiving chemotherapy with vincristine, dexamethasone, daunorubicin, and pegylated-asparaginase (PEG-Asp). He complained of a severe headache and then developed a generalized seizure at night. T1-and T2-weighted magnetic resonance imaging (MRI) and cerebral magnetic resonance venography sequences revealed superior sagittal sinus thrombosis and intrinsic hemorrhagic changes in the bilateral front-parietal lobes. He received nadroparin calcium as the anticoagulant treatment and was switched to Erwinia asparaginase (Erwinia Asp) was used instead of PEG-Asp. Oxcarbazepine and clonazepam were started with good seizure control. Intrathecal treatment was delayed until one month later. Anticoagulation treatment was stopped for 24 h prior to and 6 hours after lumbar puncture. Platelet transfusion was administered to ensure the platelet count remained >5010 9 /L. Oral acetazolamide (500-1000 mg, daily) was administered to relieve headache and reduce intracranial pressure. Three months later, brain MRI showed complete resolution or significant improvement of the filling defect. Nadroparin calcium was administered for 1 week after switching to Erwinia Asp to prevent clot recurrence. He completed the 6-month chemotherapy and is doing well with no neurological sequela, and with no recurrence of bleeding or thrombosis.Conclusions: Nadroparin calcium therapy appears to be safe and effective for pediatric CVST with ALL. Re-introduction to Erwinia Asp should be accompanied by anticoagulant therapy with nadroparin calcium.